2003
DOI: 10.1183/09031936.03.00047903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nasal or oral breathing route on upper airway resistance during sleep

Abstract: Healthy subjects with normal nasal resistance breathe almost exclusively through the nose during sleep. This study tested the hypothesis that a mechanical advantage might explain this preponderance of nasal over oral breathing during sleep.A randomised, single-blind, crossover design was used to compare upper airway resistance during sleep in the nasal and oral breathing conditions in 12 (seven male) healthy subjects with normal nasal resistance, aged 30¡4 (mean¡SEM) yrs, and with a body mass index of 23¡1 kg?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 42 publications
6
140
0
17
Order By: Relevance
“…In 1 study of sleep in normal subjects, upper airway resistance was shown to be lower with imposed nasal breathing than with imposed oral breathing, in contrast to the supine and upright awake states, in which nasal resistance is higher than oral resistance. In normal sleeping subjects, nasal breathing is expected to be the preferred route, unless it is impaired and associated with increased work of breathing or destabilized ventilation, in which case a switch to the oral route may be seen [23,24].…”
Section: Nasal Surgerymentioning
confidence: 99%
“…In 1 study of sleep in normal subjects, upper airway resistance was shown to be lower with imposed nasal breathing than with imposed oral breathing, in contrast to the supine and upright awake states, in which nasal resistance is higher than oral resistance. In normal sleeping subjects, nasal breathing is expected to be the preferred route, unless it is impaired and associated with increased work of breathing or destabilized ventilation, in which case a switch to the oral route may be seen [23,24].…”
Section: Nasal Surgerymentioning
confidence: 99%
“…1 It has been reported that upper airway collapsibility and resistance during sleep were significantly higher in subjects who were breathing through the mouth than in those who were breathing through the nose, which is different from that seen during the conscious state. 2,3 Other reasons for nasal breathing over mouth breathing during normal sleep are based on the physiological effects of decreased nasal airflow. First, bypassing the nasal airway can lead to reduced nasal receptor activation, deactivation of the nasal ventilatory reflex, and reduced spontaneous ventilation.…”
Section: Of Patterns the Nasal Airway And Sdbmentioning
confidence: 99%
“…Mouth opening increased upper airway collapsibility during sleep, which is different from that seen when awake. 2 Fitzpatrick et al 3 confi rmed that during sleep, upper airway resistance during oral breathing was 2.5 times higher than that during nasal breathing. Mouth opening may be associated with narrowing of the pharyngeal lumen and decreases in the retroglossal diameter.…”
mentioning
confidence: 99%
“…• Nocturnal mouth breathing (which is sometimes occurs in the daytime) reflects an obstruction in the nasal air passageways and the preferred route of air to reach the lungs; it implies a greater resistance to nasal air flow than to buccal air flow 26 . In healthy children, the resistance to passage of air through the mouth is greater than it is through the nose 44 and 70% of inspired air, accordingly, takes the nasal route; but in children suffering from apnea mouth breathing is a protective mechanism that is a detour around the nasal obstacles.…”
Section: -1 -Nocturnal Symptomsmentioning
confidence: 99%